A Mixed-Method Study of Medication-Related Burden Among Multi-Drug Resistant Tuberculosis Patients in West Java, Indonesia - Ausi Y; Yunivita V; Santoso P; Sunjaya DK; Barliana MI; Ruslami R (Dove Medical Press, 2024)
Yudisia Ausi,1 Vycke Yunivita,2 Prayudi Santoso,3,4 Deni Kurniadi Sunjaya,5 Melisa Intan Barliana,1,6 Rovina Ruslami2 1Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Division of Pharmacology and Therapy, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Division of Pulmonary and Critical Care, Department of Internal Medicine, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 4Hasan Sadikin General Hospital, Bandung, West Java, Indonesia; 5Department of Public Health, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 6Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Melisa Intan Barliana, Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM 21, Sumedang, West Java, 45363, Indonesia, Email melisa.barliana@unpad.ac.idBackground: Multidrug-resistant tuberculosis presents a challenging obstacle in global TB control. It necessitates complex and long-term therapy, which can potentially lead to medication-related burdens that may ultimately reduce therapy adherence and quality of life.Purpose: This study aimed to gain a deep understanding of the medication-related burdens experienced by multidrug-resistant tuberculosis patients.Methods: The study was conducted using a convergent mixed-method approach involving MDR-TB patients and their caregivers. Qualitative data were collected through semi-structured in-depth interviews, while quantitative data were gathered using the validated Living with Medicine Questionnaire 3. In the quantitative part, associations between patients' characteristics and burden levels were analysed using bivariate and multivariate analyses.Results: Seventy-four participants were involved in the study, with 71 of them completing the questionnaire and 36 participating in interviews. The qualitative results revealed the subjectivity of medication-related burden perception, which could not be fully captured by the quantitative method. Four themes of medication-related burdens emerged: personal beliefs, regimen burdens, socioeconomic burdens, and healthcare burdens. The quantitative results provided a generalized representation of the population. Age and side effects were found to be significantly associated with higher burden levels, with those aged 18- 30 having an odds ratio (OR) of 7.303 (95% CI: 1.045- 51.034), and those aged 31- 40 having an OR of 6.53 (95% CI: 1.077- 39.607). Additionally, experiencing side effects had a substantial impact, with an OR of 46.602 (95% CI: 2.825- 768.894). Both sets of results are valuable for designing patient-centered care.Conclusion: MDR-TB therapy imposes a significant burden, particularly regarding the characteristics of regimen. By understanding this burden, healthcare professionals can help improve the quality of life for these patients.Keywords: mixed method, in-depth interview, living with medicine questionnaire